Participação e controle social em Vitória: um estudo a partir do conselho municipal do idoso - Alexandre, Izabela Merisio Fernandes (2023)
This study aimed to analyze the role of the City Council for the Elderly of the city of Vitória - Comid as one of the spaces of social control, aiming to identify its interference in the elaboration, implementation and supervision of the municipal policy for the elderly in Vitória. Based on bibliographical and documentary research and semi-structured interviews, the conceptions of democracy, social participation and social control were problematized. Based on Gramsci, we understand that councils are spaces of tension, contradictory and in which different interests are in dispute. In order to understand the specificities of the rights councils for the elderly, it was necessary to understand the aging process, which is growing in the Brazilian population, which carries reflections in the social, economic, biological and behavioral fields, generating a huge challenge for social policies. Comid emerges in the midst of a context of growth in instances of social participation, at the same time that there is an advance of the neoliberal offensive throughout Brazil. Thus, we sought to characterize the social and political context of the emergence of Comid, who were the subjects involved in the process, as well as the history of participatory experiences in the municipality of Vitória. We analyzed the deliberative process at the Comid, its guidelines and its link with the demands of the elderly in Vitória, in order to identify the advances, challenges and limits of the Comid as one of the spaces for institutionalized participation and political representation of the elderly, and how it works the relationship between representative and represented within the scope of the council. We conclude that there have been advances in the Comid in relation to the implementation of policies and intersectoral articulation in the municipality of Vitória, but the council still has gaps in the effective participation of elderly people in debates and in the interlocution between representatives and represented. We understand the importance of councils as spaces that can contribute to the expansion of democracy and to guarantee rights for the elderly. However, we emphasize the importance of these spaces being politicized, qualified and occupied, in fact, by the elderly.